Women’s entrepreneurial orientation in small family firms: theorising the role of individual and family human capital - Sarto, Fabrizia; Saggese, Sara; Viganò, Riccardo (Piccola Impresa / Small Business, 2022)
Focusing on small family firms, this paper aims to provide a deeper understanding of women’s entrepreneurial orientation by exploratively assessing how it may be influenced by individual characteristics and human capital. The study draws on multiple qualitative case studies of small Italian family firms conducted between 2017 and Autumn 2021. It is grounded in 16 semi-structured interviews with women entrepreneurs in the position of owner-manager. We found that, in small family firms, conservatism and lateral thinking affect women entrepreneurs’ entrepreneurial orientation. These relationships are shaped by educational level, functional background in finance and previous experience in the family firm. The novelty of this paper relies on the conceptualisation of the implications of women’s characteristics and human capital for their entrepreneurial orientation within small family firms through ex-post propositions and a new conceptual framework. The article contributes to this special issue and the ongoing debate about women in family firms by examining the effects of human capital at both individual and family levels on women’s entrepreneurial orientation. Finally, it calls the attention of practitioners to the factors that could encourage the entry, presence and succession of women owner-managers in small family firms.